Factors that influence road accidents in Sungai Petani, Kedah / Nur Hanis Hashim and Nurhafiza Mohd Yussof - Hashim, Nur Hanis; Mohd Yussof, Nurhafiza (2019)
Approximately 1.24 million people die every year from road traffic accidents in 2010, whereas another 20 to 50 million people sustain non-fatal injuries resulting from vehicle collisions (WHO, 2013). The number of road traffic deaths annually is forecasted to increase to 1.9 million people by 2020. The current trend indicates that road traffic accidents will become the 5th leading cause of deaths by year 2030, and thus, there is a critical need to address the above issue (WHO, 2011). It is expected that China, India, Nigeria, Brazil, Indonesia, US, Pakistan, Russia, Thailand and Iran will be the countries at the forefront that contribute significantly to the number of road traffic deaths globally.